Preparation method and application of carbon / tungsten disulfide intercalation composite material
Patent Information
- Application Number
- CN202310057834.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-14
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2043-01-14
AI Technical Summary
然而,采用相同的方法,无法制备出碳/二硫化钨插层复合材料
[0026]1、本发明提出了一种高电导率、高结构稳定性的碳/二硫化钨插层复合材料的制备方法。由溶剂热制备的天然高分子/二硫化钨插层复合材料加热碳化形成的碳/二硫化钨插层复合材料,单原子碳层(石墨烯碳)均匀地嵌在二硫化钨层间,使得二硫化钨层间距从0.62纳米扩展到0.96纳米,结构稳定性更强,具有更好的力学性能以及导电能力;在生物质天然高分子与特定溶剂同时存在的前提下,才能制备出插层结构。作为对比,将碳源更换为无水葡萄糖和Super-P,或将反应溶剂更换为水,在相同的合成条件下,均无法制备出碳/二硫化钨插层复合材料,仅获得WS2/C复合材料,详见实施例4、实施例5、实施例6。
Smart Images

Figure CN116014106B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of materials preparation, and particularly relates to a method for preparing and applying a carbon / tungsten disulfide intercalated composite material. Background Technology
[0002] Tungsten disulfide is a layered compound with semiconductor properties, where the layers are bonded together only by weak van der Waals forces. Tungsten disulfide intercalation composites, formed by inserting guest materials such as inorganic or organic ions or polymers between its layers, exhibit many excellent mechanical and electrical properties. They hold broad application prospects in electrode materials, catalysts, high-elasticity new materials, coatings, pigments, sealing materials, friction materials, and desulfurization and hydrogenation agents, making them a highly promising class of functional materials.
[0003] Currently, reported alkali metal / tungsten disulfide intercalated composites are mainly prepared through solvothermal methods and direct metal vapor reaction. For example, Kopnov et al. used a two-zone vapor transport technique to intercalate WS2, embedding alkali metal atomic layers between the WS2 layers. Other reported preparation routes for tungsten disulfide intercalated composites mainly involve: first, preparing the alkali metal / tungsten disulfide intercalated compound through solvothermal or direct metal vapor reaction; second, exfoliating the tungsten disulfide in a solvent using methods such as ultrasonication, followed by cleaning to obtain a suspension of monolayer or few-layer tungsten disulfide; and third, preparing the tungsten disulfide intercalated composite through methods such as recombination, vacuum filtration, or in-situ polymerization. Intercalated composites such as polyether / WS2, polypyrrole / WS2, n-alkylamine / WS2, phenazine and p-benzoquinone / WS2, and polyether / WS2 have been reported using these methods. However, the preparation of carbon / tungsten disulfide intercalated composites is rarely reported.
[0004] Tungsten disulfide, as a multifunctional material, has broad application prospects in electrode materials due to its graphite-like layered structure, large interlayer spacing, and high theoretical capacity, particularly in sodium-ion and potassium-ion batteries. However, its low intrinsic conductivity and poor cycle stability during charge-discharge processes result in unsatisfactory electrochemical performance. Combining tungsten disulfide with carbon materials (such as graphene, carbon fibers, and carbon nanotubes) can improve these issues. For example, Jing et al. used a template method to fabricate graphene foam, then ultrasonically dispersed CNTs on the surface, added sulfur and tungsten sources, and synthesized GF@CNT@WS2 three-dimensional flexible materials through a hydrothermal reaction. If monolayer carbon is inserted as a guest into the interlayer of tungsten disulfide to prepare intercalated composite materials, maximizing the contact between tungsten disulfide and carbon atoms, the structural stability and conductivity can be further improved.
[0005] Various preparation routes for carbon / molybdenum disulfide intercalated composites have been reported for the same family of layered molybdenum disulfide. However, carbon / tungsten disulfide intercalated composites cannot be prepared using the same methods. Therefore, preparing carbon / tungsten disulfide intercalated composites using a low-cost route is both challenging and significant. Summary of the Invention
[0006] The purpose of this invention is to overcome the above-mentioned problems in the prior art and provide a method for preparing and applying a carbon / tungsten disulfide intercalated composite material. This method is simple, environmentally friendly, and low-cost. Based on biomass, it utilizes a solvothermal method to synthesize a natural polymer / tungsten disulfide intercalated composite material. In the subsequent calcination process, the biomass natural polymer carbonizes to form the carbon / tungsten disulfide intercalated composite material. Applied to sodium-ion battery anode materials, it exhibits high electron and ion transport rates and effectively improves the structural stability of tungsten disulfide, mitigating volume strain generated during charge and discharge processes. The material also possesses excellent electrochemical performance. Furthermore, this invention provides a method for preparing the intermediate product, the natural polymer / tungsten disulfide intercalated composite material, which also has broad application prospects as a functional material.
[0007] To achieve the above-mentioned technical objectives and effects, the present invention is implemented through the following technical solution:
[0008] A method for preparing a carbon / tungsten disulfide intercalated composite material, the method comprising the following steps:
[0009] (1) Pretreatment of biomass raw materials:
[0010] After crushing the biomass raw materials, they are repeatedly washed with deionized water. The crushed biomass raw materials are then filtered using deionized water and ethanol. After washing, the biomass raw materials are dried and collected.
[0011] (2) Solvothermal synthesis of biomass material precursors:
[0012] The biomass raw materials, tungsten source and sulfur source processed in step (1) are added to the reaction solvent. After adding magnetic stirring, the mixed solution is transferred to the substrate of the polytetrafluoroethylene reactor and subjected to a solvothermal reaction.
[0013] After the solvothermal reaction is completed and cooled to room temperature, the black precipitate is collected and repeatedly washed by centrifugation with deionized water and ethanol. The washed precipitate is then collected and dried to obtain the natural polymer / tungsten disulfide intercalated composite material.
[0014] (3) High-temperature treatment to synthesize carbon / tungsten disulfide intercalated composite materials:
[0015] The dried natural polymer / tungsten disulfide intercalated composite material is carbonized. The carbonization process is as follows: under an inert atmosphere, the heating rate is 1-10℃ / min, the calcination temperature is 400℃-1000℃, and the holding time is 1-6h. After cooling to room temperature, the powder is collected to obtain the carbon / tungsten disulfide intercalated composite material.
[0016] Furthermore, the biomass raw material in step (1) is one of sugarcane bagasse, grapefruit peel, and corn cob.
[0017] Furthermore, the drying temperature range in step (1) is 40-140℃.
[0018] Further, the reaction solvent in step (2) is one of acetone, N,N-dimethylformamide (DMF), dimethyl sulfoxide, and DMI.
[0019] Furthermore, in step (2), the concentration of the tungsten source in the reaction solvent ranges from 0.01 to 0.5 mol / L, and the molar ratio of the tungsten source to the sulfur source ranges from 1:1 to 1:20.
[0020] Furthermore, in step (2), the solvothermal reaction temperature range is 130-280℃, and the reaction time range is 5-25h.
[0021] Furthermore, the tungsten source is WCl6 or Na2WO4, and the sulfur source is thioacetamide (TAA) or thiourea (CH4N2S).
[0022] Furthermore, the inert atmosphere in step (3) is one of argon, nitrogen, argon / hydrogen mixture, or argon / acetylene mixture.
[0023] Further, step (3) specifically includes: heating to 700°C at a heating rate of 5°C / min and holding for 2 hours, and collecting the product after cooling to room temperature to obtain the carbon / tungsten disulfide intercalated composite material.
[0024] The present invention also provides an application of the carbon / tungsten disulfide intercalated composite material prepared by the above preparation method in the anode material of sodium-ion batteries.
[0025] The beneficial effects of this invention are:
[0026] 1. This invention proposes a method for preparing a carbon / tungsten disulfide intercalated composite material with high electrical conductivity and high structural stability. The carbon / tungsten disulfide intercalated composite material, prepared by solvothermal heating and carbonization, exhibits uniformly embedded single-atom carbon layers (graphene carbon) between the tungsten disulfide layers, expanding the interlayer spacing from 0.62 nm to 0.96 nm, resulting in stronger structural stability and better mechanical properties and electrical conductivity. The intercalated structure can only be prepared under the condition that the biomass natural polymer and a specific solvent are present simultaneously. In contrast, replacing the carbon source with anhydrous glucose and Super-P, or replacing the reaction solvent with water, under the same synthesis conditions, fails to prepare the carbon / tungsten disulfide intercalated composite material; only the WS2 / C composite material is obtained, as detailed in Examples 4, 5, and 6.
[0027] 2. The preparation process of this invention is simple and efficient, using low-cost biomass, such as sugarcane bagasse, as raw material. From the perspective of green and recyclable materials, the strategy of using biomass to synthesize electrode materials is of great significance, solving the problems of low cost and incompatibility with high electrochemical performance in current electrode material preparation. Compared with existing tungsten disulfide / carbon composite materials, the preparation process of this invention is simple, eliminating the need for multi-step synthesis. Instead, it utilizes a solvothermal method and high-temperature treatment to obtain a biomass natural polymer / tungsten disulfide intercalated composite material after the solvothermal reaction, and then obtains a carbon / tungsten disulfide intercalated composite material after high-temperature treatment.
[0028] 3. The preparation method of the carbon / tungsten disulfide intercalated composite material of the present invention involves converting biomass into single-atom carbon layers (graphene carbon) and uniformly embedding them in the interlayer space of tungsten disulfide. While ensuring high conductivity, the interlayer space of tungsten disulfide is increased. The extremely wide interlayer space allows for rapid electrolyte penetration, improved ion transport kinetics, and easier insertion of sodium ions. At the same time, the high structural stability greatly alleviates the volume expansion problem when used as an electrode material, thereby synergistically improving electrochemical performance in multiple aspects. Attached Figure Description
[0029] The accompanying drawings, which are included to provide a further understanding of the invention and form part of this application, illustrate exemplary embodiments of the invention and, together with their description, serve to explain the invention and do not constitute an undue limitation thereof. In the drawings:
[0030] Figure 1 The XRD patterns of the precursor and product of the carbon / tungsten disulfide intercalated composite material in Example 1 are shown in comparison.
[0031] Figure 2 SEM image of the carbon / tungsten disulfide intercalated composite material of Example 1;
[0032] Figure 3HRTEM image of the carbon / tungsten disulfide intercalated composite material of Example 1;
[0033] Figure 4 The graph shows the cycling performance of the carbon / tungsten disulfide intercalated composite material of Example 1 as a sodium-ion battery anode material at a current density of 0.2 A / g.
[0034] Figure 5 The graph shows the cycling performance of the carbon / tungsten disulfide intercalated composite material of Example 1 as a sodium-ion battery anode material at a current density of 1 A / g.
[0035] Figure 6 The XRD pattern of the carbon / tungsten disulfide intercalated composite material prepared in Example 2 using acetone instead of DMF as the reaction solvent;
[0036] Figure 7 The XRD pattern of the carbon / tungsten disulfide intercalated composite material prepared by replacing sugarcane bagasse with corn cob as the carbon source in Example 3;
[0037] Figure 8 The XRD pattern of the WS2 / C composite material prepared using water as the reaction solvent in Example 4 is shown below.
[0038] Figure 9 The XRD pattern of the WS2 / C composite material prepared in Example 5 using anhydrous glucose instead of biomass material as the carbon source;
[0039] Figure 10 The XRD pattern of the WS2 / C composite material prepared by replacing biomass materials with Super-P as the carbon source in Example 6 is shown below. Detailed Implementation
[0040] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0041] Example 1
[0042] (1) Pretreatment of biomass raw materials: After cutting the sugarcane bagasse, wash it repeatedly with distilled water. Use deionized water and ethanol to filter the crushed sugarcane bagasse. After collecting the washed sugarcane bagasse, put it into the first blast oven to dry and collect it. The drying temperature is 60℃.
[0043] (2) Solvent-thermal synthesis of natural polymer / tungsten disulfide intercalated composite material precursor: Sugarcane bagasse, WCl6 and TAA treated in step (1) were added to DMF. The concentration of WCl6 in DMF was 0.1 mol / L and the molar ratio of WCl6 to TAA was 1:4. After stirring with a magnetic stirrer for 5 min, the mixed solution was transferred to the substrate of a polytetrafluoroethylene reactor and placed in a second blower oven for solvothermal reaction. The reaction temperature was 200℃ and the reaction time was 24 h.
[0044] After the solvothermal reaction was completed and cooled to room temperature, the black precipitate was collected and placed in a centrifuge tube. It was then repeatedly washed by centrifugation with deionized water and ethanol. The washed precipitate was then collected in a beaker and dried to obtain the precursor of the natural polymer / tungsten disulfide intercalated composite material.
[0045] (3) High-temperature treatment to synthesize carbon / tungsten disulfide intercalated composite material: The dried natural polymer / tungsten disulfide intercalated composite material precursor is placed in a ceramic boat and calcined in a tube furnace for high-temperature carbonization. The carbonization process is as follows: under an argon atmosphere, the heating rate is 5℃ / min, the calcination temperature is 700℃, and the holding time is 2h. After the tube furnace cools down to room temperature, the powder in the ceramic boat is collected to obtain the carbon / tungsten disulfide intercalated composite material.
[0046] Figure 1 A comparison of the XRD patterns of the natural polymer / tungsten disulfide intercalated composite precursor and the carbon / tungsten disulfide intercalated composite reveals that the (002) interplanar spacing of the tungsten disulfide in the precursor has expanded to 0.98 nm after the solvothermal reaction. After high-temperature treatment, the precursor is transformed into a carbon / tungsten disulfide intercalated composite, and the XRD pattern of the product shows that its (002) interplanar spacing is 0.96 nm.
[0047] Figure 2 Scanning electron microscopy of the carbon / tungsten disulfide intercalated composite material. The spherical carbon / tungsten disulfide intercalated composite material is embedded in a biomass carbon matrix. The diameter of the carbon / tungsten disulfide intercalated composite material spheres is approximately 0.8 micrometers.
[0048] Figure 3 The image shows a transmission electron microscope (TEM) image of the carbon / tungsten disulfide intercalated composite material, indicating that the interlayer spacing of the carbon / tungsten disulfide intercalated composite material is 0.96 nm.
[0049] Battery performance test:
[0050] The carbon / tungsten disulfide intercalated composite material prepared in Example 1 was uniformly mixed with carbon black conductive agent (Super-P) and polyvinylidene fluoride (PVDF) binder at a mass ratio of 7:2:1. Methylpyrrolidone (NMP) was then added as a solvent, and the mixture was prepared into a slurry by ball milling. The slurry was then uniformly coated onto copper foil and placed in a vacuum drying oven to dry at 70°C for 12 hours to obtain the carbon / tungsten disulfide intercalated composite material electrode.
[0051] The prepared electrodes were cut into 12 mm diameter battery electrode sheets for assembling a CR2025 button sodium-ion battery. The steps were as follows: in an argon-atmospheric glove box, using a sodium sheet as the counter electrode, glass microfiber (Whatman, GF / A) as the separator, and a 1.0 mol / L propylene carbonate (PC) solution with NaClO4 as the electrolyte, the battery was assembled. Electrochemical performance was tested using a LandCT2001A battery testing platform.
[0052] Figure 4 The electrode prepared for Example 1, as the negative electrode of a sodium-ion battery, exhibits the following cycling performance at a current density of 0.2 A / g: discharge capacity of 390 mAh / g and coulombic efficiency of 100%. Figure 5 The electrode prepared in Example 1, as a sodium-ion battery anode, exhibits the following cycling performance at a high current density of 1 A / g: discharge capacity of 350 mAh / g and coulombic efficiency of 100%. It is a sodium-ion battery anode material with high capacity, high structural stability, long cycle life, and fast charge-discharge capability.
[0053] Example 2
[0054] (1) Pretreatment of biomass raw materials: After cutting the sugarcane bagasse, wash it repeatedly with distilled water. Use deionized water and ethanol to filter the crushed sugarcane bagasse. After collecting the washed sugarcane bagasse, put it into the first blast oven to dry and collect it. The drying temperature is 40℃.
[0055] (2) Solvent thermal synthesis of natural polymer / tungsten disulfide intercalated composite material precursor: Sugarcane bagasse, Na2WO4 and TAA treated in step (1) were added to acetone. The concentration of Na2WO4 in acetone was 0.01 mol / L and the molar ratio of Na2WO4 to TAA was 1:1. After stirring with a magnetic stirrer for 10 min, the mixed solution was transferred to the substrate of a polytetrafluoroethylene reactor and placed in a second blower oven for hydrothermal reaction. The reaction temperature was 200℃ and the reaction time was 5 h.
[0056] After the solvothermal reaction was completed and cooled to room temperature, the black precipitate was collected and placed in a centrifuge tube. It was then repeatedly washed by centrifugation with deionized water and ethanol. The washed precipitate was then collected in a beaker and dried to obtain the precursor of the natural polymer / tungsten disulfide intercalated composite material.
[0057] (3) High-temperature treatment to synthesize carbon / tungsten disulfide intercalated composite material: The dried natural polymer / tungsten disulfide intercalated composite material precursor is placed in a ceramic boat and calcined in a tube furnace for high-temperature carbonization. The carbonization process is as follows: under an argon atmosphere, the heating rate is 1℃ / min, the calcination temperature is 400℃, and the holding time is 1h. After the tube furnace cools down to room temperature, the powder in the ceramic boat is collected to obtain the carbon / tungsten disulfide intercalated composite material. Figure 6 The XRD pattern of the synthesized carbon / tungsten disulfide intercalated composite material shows that the (002) interplanar spacing of the tungsten disulfide in the product has been extended to 0.96 nm, indicating that carbon / tungsten disulfide intercalated composite material can still be synthesized after replacing DMF with acetone as the reaction solvent.
[0058] Example 3
[0059] (1) Pretreatment of biomass raw materials: After the corn cobs are cut, they are repeatedly washed with distilled water. The broken corn cobs are filtered with deionized water and ethanol. The washed corn cobs are collected and dried in the first blast oven at a temperature of 140°C.
[0060] (2) Solvent thermal synthesis of natural polymer / tungsten disulfide intercalated composite material precursor: Corn cob, WCl6 and CH4N2S treated in step (1) were added to DMF. The concentration of WCl6 in DMF was 0.5 mol / L and the molar ratio of WCl6 to CH4N2S was 1:20. After stirring with a magnetic stirrer for 10 min, the mixed solution was transferred to the substrate of the pPL reactor and placed in the second blower oven for hydrothermal reaction. The reaction temperature was 270℃ and the reaction time was 25 h.
[0061] After the solvothermal reaction was completed and cooled to room temperature, the black precipitate was collected and placed in a centrifuge tube. It was then repeatedly washed by centrifugation with deionized water and ethanol. The washed precipitate was then collected in a beaker and dried to obtain the precursor of the natural polymer / tungsten disulfide intercalated composite material.
[0062] (3) High-temperature treatment to synthesize carbon / tungsten disulfide intercalated composite material: The dried natural polymer / tungsten disulfide intercalated composite material precursor is placed in a ceramic boat and calcined in a tube furnace for high-temperature carbonization. The carbonization process is as follows: under an argon / hydrogen mixed atmosphere, the heating rate is 10℃ / min, the calcination temperature is 1000℃, and the holding time is 6h. After the tube furnace cools down to room temperature, the powder in the ceramic boat is collected to obtain the carbon / tungsten disulfide intercalated composite material. Figure 7The XRD pattern of the synthesized carbon / tungsten disulfide intercalated composite material shows that the (002) interplanar spacing of the tungsten disulfide in the product has been expanded to 0.96 nm, indicating that carbon / tungsten disulfide intercalated composite material can still be synthesized after replacing sugarcane bagasse with corn cob as carbon source.
[0063] Example 4
[0064] (1) Pretreatment of biomass raw materials: After cutting the sugarcane bagasse, wash it repeatedly with distilled water. Use deionized water and ethanol to filter the crushed sugarcane bagasse. After collecting the washed sugarcane bagasse, put it into the first blast oven to dry and collect it. The drying temperature is 60℃.
[0065] (2) Hydrothermal synthesis of WS2 / C precursor: Sugarcane bagasse, WCl6 and TAA treated in step (1) were added to deionized water. The concentration of WCl6 in deionized water was 0.1 mol / L and the molar ratio of WCl6 to TAA was 1:4. After stirring with a magnetic stirrer for 10 min, the mixed solution was transferred to a polytetrafluoroethylene reactor substrate and placed in a second blower oven for hydrothermal reaction. The reaction temperature was 200℃ and the reaction time was 24 h.
[0066] After the hydrothermal reaction was completed and cooled to room temperature, the black precipitate was collected and placed in a centrifuge tube. It was then repeatedly washed by centrifugation with deionized water and ethanol. The washed precipitate was then collected in a beaker and dried to obtain the WS2 / C precursor.
[0067] (3) High-temperature treatment to synthesize WS2 / C composite material: The dried WS2 / C precursor is placed in a ceramic boat and calcined in a tube furnace for high-temperature carbonization. The carbonization process is as follows: under an argon atmosphere, the heating rate is 5℃ / min, the calcination temperature is 700℃, and the holding time is 2h. After the tube furnace cools down to room temperature, the powder in the ceramic boat is collected to obtain the WS2 / C composite material. Figure 8 The XRD pattern of the synthesized WS2 / C composite material shows that the (002) interplanar spacing of WS2 in the product is 0.62 nm, and there is no layer expansion phenomenon. This indicates that under the same conditions, it is impossible to synthesize carbon / tungsten disulfide intercalated composite material by simply changing the reaction solvent from DMF to water.
[0068] Example 5
[0069] (1) Solvent-thermal synthesis of WS2 / C precursor: Anhydrous glucose, WCl6 and TAA were added to DMF. The concentration of WCl6 in DMF was 0.1 mol / L, the concentration of anhydrous glucose in DMF was 5%, and the molar ratio of WCl6 to TAA was 1:4. After stirring with a magnetic stirrer for 10 min, the mixed solution was transferred to a polytetrafluoroethylene reactor substrate and placed in a second blower oven for hydrothermal reaction. The reaction temperature was 200℃ and the reaction time was 24 h.
[0070] After the solvothermal reaction is completed and cooled to room temperature, the black precipitate is collected and placed in a centrifuge tube. It is then repeatedly washed by centrifugation with deionized water and ethanol. The washed precipitate is then collected in a beaker and dried to obtain the WS2 / C precursor.
[0071] (2) High-temperature treatment to synthesize WS2 / C composite material: The dried precursor is placed in a ceramic boat and calcined in a tube furnace for high-temperature carbonization. The carbonization process is as follows: under an argon atmosphere, the heating rate is 5℃ / min, the calcination temperature is 700℃, and the holding time is 2h. After the tube furnace cools down to room temperature, the powder in the ceramic boat is collected to obtain the WS2 / C composite material. Figure 9 The XRD pattern of the synthesized WS2 / C composite material shows that the (002) interplanar spacing of WS2 in the product is 0.62 nm, and there is no layer expansion phenomenon. This indicates that under the same conditions, it is impossible to synthesize carbon / tungsten disulfide intercalated composite material by simply replacing the carbon source with anhydrous glucose instead of biomass material.
[0072] Example 6
[0073] (1) Solvent-thermal synthesis of WS2 / C precursor: Super-P, WCl6 and TAA were added to DMF. The concentration of WCl6 in DMF was 0.1 mol / L, the concentration of Super-P in DMF was 5%, and the molar ratio of WCl6 to TAA was 1:4. After stirring with a magnetic stirrer for 10 min, the mixed solution was transferred to a polytetrafluoroethylene reactor substrate and placed in a second blower oven for hydrothermal reaction. The reaction temperature was 200℃ and the reaction time was 24 h.
[0074] After the solvothermal reaction is completed and cooled to room temperature, the black precipitate is collected and placed in a centrifuge tube. It is then repeatedly washed by centrifugation with deionized water and ethanol. The washed precipitate is then collected in a beaker and dried to obtain the WS2 / C precursor.
[0075] (2) High-temperature treatment to synthesize WS2 / C composite material: The dried precursor is placed in a ceramic boat and calcined in a tube furnace for high-temperature carbonization. The carbonization process is as follows: under an argon atmosphere, the heating rate is 5℃ / min, the calcination temperature is 700℃, and the holding time is 2h. After the tube furnace cools down to room temperature, the powder in the ceramic boat is collected to obtain the WS2 / C composite material. Figure 10 The XRD pattern of the synthesized WS2 / C composite material shows that the (002) interplanar spacing of WS2 in the product is 0.62 nm, and there is no layer expansion phenomenon. This indicates that under the same conditions, it is impossible to synthesize carbon / tungsten disulfide intercalated composite material by simply replacing the carbon source with Super-P instead of biomass material.
[0076] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0077] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claimed invention.
Claims
1. A method for preparing a carbon / tungsten disulfide intercalated composite material, characterized in that: The method includes the following steps: (1) Pretreatment of biomass raw materials: The biomass raw materials are crushed and repeatedly washed with deionized water. The crushed biomass raw materials are then filtered using deionized water and ethanol. The washed biomass raw materials are dried and collected. The biomass raw materials are one of sugarcane bagasse, grapefruit peel, and corn cob. The drying temperature range is 40-140℃. (2) Solvent-thermal synthesis of biomass material precursors: The biomass raw materials, tungsten source and sulfur source processed in step (1) are added to the reaction solvent. After stirring with a magnetic stirrer, the mixed solution is transferred to the substrate of a polytetrafluoroethylene reactor and subjected to a solvothermal reaction. After the solvothermal reaction is completed and cooled to room temperature, the black precipitate is collected and repeatedly washed by centrifugation with deionized water and ethanol. The washed precipitate is then collected, dried, and the natural polymer / tungsten disulfide intercalated composite material is obtained. The reaction solvent is one of acetone, N,N-dimethylformamide (DMF), dimethyl sulfoxide, and DMI. The concentration of the tungsten source in the reaction solvent ranges from 0.01 to 0.5 mol / L, and the molar ratio of the tungsten source to the sulfur source ranges from 1:1 to 1:
20. The solvothermal reaction temperature ranges from 130 to 280℃, and the reaction time ranges from 5 to 25 h. The tungsten source is WCl6 or Na2WO4, and the sulfur source is thioacetamide (TAA) or thiourea. (3) High-temperature treatment to synthesize carbon / tungsten disulfide intercalated composite materials: The dried natural polymer / tungsten disulfide intercalated composite material was carbonized. The carbonization process was as follows: under an inert atmosphere, the temperature was raised to 700℃ at a heating rate of 5℃ / min and held for 2 hours. After cooling to room temperature, the product was collected to obtain the carbon / tungsten disulfide intercalated composite material. The inert atmosphere was one of argon, nitrogen, argon / hydrogen mixture, or argon / acetylene mixture.
2. The application of a carbon / tungsten disulfide intercalated composite material prepared by the preparation method of claim 1 in the anode material of sodium-ion batteries.
Citation Information
Patent Citations
MoS2 / C superlattice heterojunction nano-sheet self-assembled nano-tube as well as preparation method and application thereof
CN105206807A
Metal sulfide / carbon composite material, preparation method of the same, and application of the same in cell cathode materials
CN109546139A